2020
DOI: 10.1098/rspb.2019.2952
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in unnatural times: illuminated night negatively affects sleep and associated hypothalamic gene expressions in diurnal zebra finches

Abstract: We investigated the effects of exposure at ecologically relevant levels of dim light at night (dLAN) on sleep and the 24 h hypothalamic expression pattern of genes involved in the circadian timing ( per2, bmal1 , reverb-β , cry1 , ror-α , clock ) and sleep regulatory pathways (cytokines: tlr4 , tnf - α , il-1β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
1
25
1
Order By: Relevance
“…Sampled within a day after being brought into captivity, urban birds showed clear advances in the circadian system, including, as in our birds, in hypothalamic BMAL1. Other experimental studies have also confirmed effects of ALAN on avian rhythms in brain and other tissues (16,17). In our study, only some of the investigated regulatory genes aligned with the ALANdependent advances of rhythms in behavior and BMAL1.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Sampled within a day after being brought into captivity, urban birds showed clear advances in the circadian system, including, as in our birds, in hypothalamic BMAL1. Other experimental studies have also confirmed effects of ALAN on avian rhythms in brain and other tissues (16,17). In our study, only some of the investigated regulatory genes aligned with the ALANdependent advances of rhythms in behavior and BMAL1.…”
Section: Discussionmentioning
confidence: 80%
“…In free-living and captive organisms, altered daily and annual activity has been widely reported, and experimental illumination has confirmed causal effects of ALAN (11,12). Still, it is largely unclear whether the circadian system, its multiple components, and the physiological pathways it coordinates, remain synchronized with activity patterns (13)(14)(15)(16)(17)(18). ALAN has also been shown to induce physiological changes, including in endocrine, immune and metabolic pathways (15,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies also found that when exposed to artificial light at night, birds show increased activity [ 44 , 55 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], delayed chirping behavior [ 74 ], increased vigilance [ 75 ] and reduced sleep behavior at night [ 43 , 76 , 77 , 78 , 79 ], but see [ 80 , 81 ]. There is some evidence that these changes in behavior are associated with reduced circulating oxalate [ 66 , 79 ], a biomarker of sleep debt in rats and humans [ 82 ]. However, other studies found an increase [ 83 ] or no change [ 84 ] in oxalate under artificial light at night, raising the possibility that the level of oxalate does not reflect prior sleep/wake history in birds [ 84 ].…”
Section: Light Regulates and Suppresses Sleep In Diurnal Birdsmentioning
confidence: 99%
“…However, other studies found an increase [ 83 ] or no change [ 84 ] in oxalate under artificial light at night, raising the possibility that the level of oxalate does not reflect prior sleep/wake history in birds [ 84 ]. In captive zebra finches ( Taeniopygia guttata ), artificial light at night has also been found to alter expression of genes involved in sleep regulation [ 79 ]. Together, these studies provide accumulating evidence for disruptive effects of artificial lighting on avian sleep.…”
Section: Light Regulates and Suppresses Sleep In Diurnal Birdsmentioning
confidence: 99%
See 1 more Smart Citation